Characteristics of relations in ecological-economic control of heat-power objects systems using reagent-free water preparation - Zhuravska, Nataliia E. (Journal of the Belarusian State University. Ecology, 2021)
The article proposes a methodology taking into account the system-generalized approach (Approach, Theory), which allows not only to correctly assess, but also to select the optimal loads on a heat-and-power facility, for heat supply systems, using reagent-free water treatment, but also to predict the consequences of technogenic influences. The external ecological and economic impacts are also analyzed. Considered and established, on a priority basis, for systems of heat and power facilities, about the influence of environmental situations and their formation under the influence of external factors among themselves.